2015
DOI: 10.1167/iovs.14-15549
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Childhood Myopia: Findings From the NICER Study

Abstract: In NI children, parental history of myopia and type of schooling are important determinants of myopia. The association between myopia and an environmental factor, such as physical activity levels, may provide insight into preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 46 publications
5
75
2
1
Order By: Relevance
“…O'Donoghue et al. () presented results from The Northern Ireland Childhood Error of Refraction (NICER) study. Northern Irish children ( n = 661) aged 12–13 were recruited from a stratified random sample of schools, representative of the population of UK.…”
Section: Resultsmentioning
confidence: 99%
“…O'Donoghue et al. () presented results from The Northern Ireland Childhood Error of Refraction (NICER) study. Northern Irish children ( n = 661) aged 12–13 were recruited from a stratified random sample of schools, representative of the population of UK.…”
Section: Resultsmentioning
confidence: 99%
“…2010), and the NICER study in Northern Ireland reported a prevalence of 17.7% (≤−0.50 D) at approximately 13 years of age (O'Donoghue et al. 2015). The multi‐ethnic Collaborative Longitudinal Evaluation of Ethnicity and Refractive Error (CLEERE) study conducted in the US found a prevalence of 11.6% (≤−0.75 D in both meridians) in 10‐year‐old (Zadnik et al.…”
Section: Discussionmentioning
confidence: 99%
“…5,13,[41][42][43][44][45][46][47] Moreover, cognitive ability may be associated with myopia primarily through its impact on educational behavior.…”
Section: Discussionmentioning
confidence: 99%